2018
DOI: 10.1155/2018/9379608
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Implant and New Rehabilitation for Better Esthetics

Abstract: Tooth loss can result in loss of facial esthetics, in addition to its effect on mastication, swallowing, and speech. Adequate planning is required in order for the prosthetic treatment of the teeth and implants to be successful. Here, we present a clinical case demonstrating that improper positioning of an implant can make prosthetic rehabilitation unfeasible, necessitating new surgical and rehabilitation planning to achieve the desired esthetics. The patient had a missing right lateral incisor and cuspid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Dental implant therapy is the most conservative treatment option for the lost dentition [1]. Despite the high success rate of this treatment modality, long-term follow-up studies have shown unesthetic results and the need for additional surgical procedures [2], resulting in implant removal and/or additional procedures to recover hard and soft tissue losses [3]. Clinical demand focused on reduction of dental implant therapy time has lead research studies in the field of immediate implant placement 4].…”
Section: Introductionmentioning
confidence: 99%
“…Dental implant therapy is the most conservative treatment option for the lost dentition [1]. Despite the high success rate of this treatment modality, long-term follow-up studies have shown unesthetic results and the need for additional surgical procedures [2], resulting in implant removal and/or additional procedures to recover hard and soft tissue losses [3]. Clinical demand focused on reduction of dental implant therapy time has lead research studies in the field of immediate implant placement 4].…”
Section: Introductionmentioning
confidence: 99%